Avaliação dos Cerrados de Minas Gerais e indicação de áreas potenciais para preservação - Lima, Samuel do Carmo; Rosa, Roberto; Baccaro, Claudete Aparecida Dellevedove; Guimarães , Regina Maia; das Chagas, Ivo (Sociedade & Natureza, 2021)
Avaliação dos Cerrados de Minas Gerais e indicação de áreas potenciais para preservação